COGNITIVE AND SOCIAL ASPECTS OF COMPUTER-MEDIATED WORK: Toward a framework for understanding working life - Løw Aboulafia, Annette (Psyke & Logos, 2001)
Much IT research and practice attempts to understand and design for the interaction between human beings and computers. This paper focuses on the two most well-known approaches in this area, namely Human-Computer Interaction (HCI) and Computer Supported Cooperative Work (CSCW)2. I argue that HCI and CSCW reflect different aspects of human activity, which can be characterized as the cognitive and the social aspects of systems design. This paper examines these two approaches rom a (meta)theoretical point of view focusing on their ‘unit of analysis’, as well as their underlying philosophical assumptions. It is argued that the two approaches draw on distinct and somewhat contradictory philosophical ideas and theories, and consequently suggest different solutions to the design of computer systems. Much HCI work adapts a cognitive psychological perspective, focusing on the cognitive aspect of systems design, whereas CSCW work takes on a sociological perspective dealing with social and organisational aspects of systems design. In order to achieve a more ‘coherent’ understanding of systems design and computer-mediated work we need to ‘integrate’ the cognitive perspective (internal thought processes) and the social perspective (external social behaviour). Based on a dialectical-materialistic philosophy and the psychological approach developed from such principles, that of Activity Theory, I situate cognitive and the social activity within a broader framework for working life.